The Effect of Investment and Consumption on Economic Growth - Ather Aldin; Monjeed Alneil (Newinera Publisher, 2021)
The purpose of this research is to establish whether or not there is a relationship between investment and consumption levels and economic growth. This study employs quantitative methods, and the data is processed in accordance with the requirements of the model being utilized. Multiple linear regression is the method used in the data processing. The information utilized is secondary information derived from historical documents or reports that have been published or are in the process of being published. The findings revealed that the investment variable had a positive and statistically significant impact on economic growth. Conclusions While the variable level of consumption has a positive and substantial impact on economic development, the level of consumption is not constant. According to the results of the regression, the value of R-Squared (R2) is 0.726. Thus, the independent variable can explain 85.2 percent of the variance in economic growth, with the remaining 0.15 percent explained by factors outside the model, as shown in Figure 1. It is proposed to the government that it raise the proportion of development expenditures, with the expectation that these expenditures would be used toward improving development and public infrastructure in order to promote the smooth operation of economic activities